Flavonoid Analysis and Antioxidant Activities of the Bryonia alba L. Aerial Parts - Irina Ielciu; Michel Frédérich; Daniela Hanganu; Luc Angenot; Neli-Kinga Olah; Allison Ledoux; Gianina Crișan; Ramona Păltinean (MDPI AG, 2019)
Bryonia alba L. is the only Bryonia species found in Romanian flora, being known as a remedy for inflammatory pathologies or for its hepatoprotective and adaptogen activities. The present investigation studied the flavonoid composition and antioxidant activities of the aerial parts of this species. Flavonoid profile was evaluated by HPLC coupled with Diode Array Detection (DAD), while antioxidant capacity was assessed by various methods, testing different antioxidant mechanisms: DPPH (2,2-diphenyl-1-picrylhydrazyl), CUPRAC (cupric reducing antioxidant capacity), FRAP (ferric reducing ability of plasma), TEAC (Trolox equivalent antioxidant capacity), EPR (electron paramagnetic resonance method) and SNPAC (silver nanoparticles antioxidant capacity). Cytotoxicity was tested on human cancerous and healthy cell lines. Anti-plasmodial tests were performed on two strains of Plasmodium falciparum. Whole organism toxicity was assessed on zebrafish larvae. The HPLC-DAD analysis proved the presence of lutonarin, saponarin, isoorientin, and isovitexin as the major flavonoids in the composition of tested samples. Significant results were obtained for all antioxidant capacity assays. The cytotoxicity tests proved the absence of cellular and parasitic toxicity and these results were confirmed by the lack of toxicity on the zebrafish larvae model. This study proves a promising potential of the aerial parts of Bryonia alba L. as antioxidant agents.